THE STATISTICAL METHOD FOR FINDING THE RESPONSE FOR N RANDOM EXCITATION OF THE INVERTED PENDULUM - Marinică STAN; Petre STAN (Fiabilitate şi Durabilitate)
We present a method for estimating the power spectral density of the stationary response of oscillatorwith a nonlinear restoring force under external stochastic wide-band excitation. An equivalent linear system isderived, from which the power spectral density is deduced. We consider an inverted pendulum suspendedsubjected to white noise excitation with a random number n random excitations simultaneously applied. Themethod will be briefly discussed in the following sections